Geotourism and Sustainability as a Business Mindset. Issue 3 (2nd April 2016) - Jorgenson, Jake; Nickerson, Norma
Abstract : Geotourism sustains and/or enhances the geographical character of a place, embracing the environment, heritage, aesthetics, culture, and well-being of its residents. Geotourism promotes behaviors such as buying local products, improving employee well-being, and donating to local causes. Visitors to Montana have been previously identified as geotravelers, which influenced the Montana Office of Tourism to target this segment. While previous studies confirmed the demand for geotourism in Montana, little research had examined the supply-side perspective on practicing the sustainable initiative tourists/geotravelers expect. By using geotourism's constructs, this study assessed the extent to which Montana's tourism and hospitality businesses have adopted geotourism's principles in their business mindset. Results of a web-based survey indicate moderate to low participation by Montana businesses. Further analysis reveals incongruity in behavior by business sector. Smaller businesses appear less sustainable and geo-savvy. Findings have implications for understanding the demand side of geotourism and strengthen previous research implementing sustainable practices.